JAK-STAT-mediated chronic inflammation impairs cytotoxic T lymphocyte activation to decrease anti-PD-1 immunotherapy efficacy in pancreatic cancer. (4th March 2017) - Lu, Chunwan; Talukder, Asif; Savage, Natasha M.; Singh, Nagendra; Liu, Kebin
ABSTRACT: Human pancreatic cancer does not respond to immune check point blockade immunotherapy. One key feature of pancreatic cancer is the association between its progression and chronic inflammation. Emerging evidence supports a key role for the JAK-STAT pathway in pancreatic cancer inflammation. We aimed at testing the hypothesis that sustained JAK-STAT signaling suppresses cytotoxic T lymphocyte (CTL) activation to counteract anti-PD-1 immunotherapy-induced CTL activity in pancreatic cancer. We show that human pancreatic carcinomas express high level of PD-L1 and exhibit low level of CTL infiltration. JAK-STAT inhibitor Ruxolitinib selectively inhibits STAT1 and STAT3 activation and increases CTL infiltration to induce a Tc1/Th1 immune response in the tumor microenvironment in an orthotopic pancreatic cancer mouse model. Ruxilitinib-mediated tumor suppressive efficacy diminishes in T-cell-deficient mice. Pancreatic tumor grows significantly faster in IFNγ-deficient mice. However, neutralizing IFNγ does not alter tumor growth but diminishes Ruxolitinib-induced tumor suppression in vivo, indicating that lymphocytes and IFNγ are essential for Ruxolitinib-induced host antitumor immune response. Both type I and type II interferons upregulate PD-L1 expression through the JAK-STAT signaling pathway in mouse pancreatic tumor cells. Tumor cells respond to activated T cells by activating STAT3. The inhibition of STAT3 downregulates immune suppressive cytokines production by tumor cells, resulting in increased T cell activation and effector function. Consequently, Ruxolitinib significantly improves the efficacy of anti-PD-1 immunotherapy. Our data demonstrate that Ruxolitinib is effective in the inhibition of systemic inflammation in the tumor microenvironment and therefore upregulates CTL infiltration and activation to overcome pancreatic cancer resistance to anti-PD-1 immunotherapy.